Objetos educacionais virtuais em livros didáticos de física: limites e potencialidades - Rezende, Thaianne Lopes de Souza (2019)
This thesis contemplates the results of an analysis of Physics textbooks regarding the presentation of virtual educational objects and their articulation with typical high school contexts. We aim to understand the main characteristics of these objects, in addition to analyzing their limits and potentialities, since, although often proposed, they are not used in the classroom. We present a bibliographic survey on the theme and the results obtained in the analysis of the three volumes of one of the collections used in public schools and approved under the National Textbook Program in 2015 and 2018. In order to understand how OEVs are proposed, we generally analyzed one of the proposed objects in the PISA test in 2015, also taking a qualitative approach through content analysis. From the obtained results it was possible to conclude that the virtual educational objects are proposed in expressive quantity, but still do not have attributes (viability and orientations regarding their pedagogical use) that highlight them as a more advantageous resource in relation to the printed text in the usual conditions found in classrooms. However, we understand the function of these objects as an approximation between the concepts involved and a context more familiar or accessible to the student. Thus, we approach its limitations and potentialities, establishing a parallel with didactic strategies based on analogies and metaphors proposed in the area of Science/Physics Teaching. From the results, we discuss possibilities for effective insertion of virtual educational objects in the classroom aiming at effective learning.